Proceedings of the International Conference on Teacher Training and Education 2017 (ICTTE 2017) 2017
DOI: 10.2991/ictte-17.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students' Difficulties and Needs in Essay Writing

Abstract: Having observed the writing class and EFL students" essays in previous semester, the researchers found that their essay were in poor quality. This situation portrays the fact that writing is a complex skill to learn in English language acquisition. This study is aimed to investigate the difficulties faced by EFL students in essay writing as well as exploring their learning needs to have better quality of English composition. Examining essays and administering open-ended questionnaires were done to 33 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
79
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 10 publications
15
79
2
Order By: Relevance
“…Moreover, the studies of Rasyidah & Antoni (2014), Cahyono et al (2016), and Irwan et al (2018), similarly reported that the Indonesian EFL students' academic essay writing ability was satisfied. However, the result of this current study was irrelevant found by the studies of Eliwarti & Maarof (2014), Wigati (2014), Nugraha (2015), Aunurrahman, Hamied & Emilia (2016), and Ariyanti & Fitriana (2017) reported that the writing ability of Indonesian university EFL students was poor quality in essay academic writing performance. Highlighting the findings of these previous studies and this current study, it could be stated that there was any improvement of the Indonesian EFL students' essay writing ability.…”
Section: E Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Moreover, the studies of Rasyidah & Antoni (2014), Cahyono et al (2016), and Irwan et al (2018), similarly reported that the Indonesian EFL students' academic essay writing ability was satisfied. However, the result of this current study was irrelevant found by the studies of Eliwarti & Maarof (2014), Wigati (2014), Nugraha (2015), Aunurrahman, Hamied & Emilia (2016), and Ariyanti & Fitriana (2017) reported that the writing ability of Indonesian university EFL students was poor quality in essay academic writing performance. Highlighting the findings of these previous studies and this current study, it could be stated that there was any improvement of the Indonesian EFL students' essay writing ability.…”
Section: E Discussioncontrasting
confidence: 77%
“…Seeing the differences research findings concerning the Indonesian EFL students' essay writing performance i.e. studies from Eliwarti & Maarof (2014); Aunurrahman, Hamied & Emilia (2016); and Ariyanti & Fitriana, (2017), they revealed low writing ability. Meanwhile, the studies from Rasyidah & Antoni (2014); Cahyono et al (2016); Sanu (2016); Husin & Nurbayani (2017); and Irwan et al (2018) highlighted high writing ability, indeed it could be said that the essay writing ability of EFL students in Indonesia is still debatable issues in research communities.…”
Section: A Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, the contents of common writing courses at tertiary levels were not accordingly aligned and compatible with the specific disciplinary content and written discourse of target students' particular fields of study although there may be arbitrary relevance between texts and thematic areas of random fields of study. There was no compatibility of common writing courses with target disciplinary content; this is consistent with Ariyanti and Fitriana (2017), Cahyono et al (2016), Husin and Nurbayani (2017), Rogers (2010), and Thesen (2013).…”
Section: Discussionsupporting
confidence: 73%